Irreversible organ damages in patients with systemic lupus erythematosus. SLICC damage index - E. S. Solovyeva; E. A. Aseeva; T. A. Lisitsyna; T. V. Popkova; S. K. Solovyev; E. L. Nasonov (Современная ревматология, 2016)
The paper presents a literature review demonstrating the importance of using the damage index (DI) for the comprehensive evaluation of the degree of irreversible organ changes in patients with systemic lupus erythematosus (SLE). The need and prerequisites for creating this reliable tool developed by the Systemic Lupus International Collaborating Clinics (SLICC) Group in 1996 have been substantiated. The emergence of DI is emphasized to be associated with higher survivals in patients with SLE in the past decades and with an increase of their irreversible organ damages that were a consequence of both disease activity and performed therapy. Particular attention is given to the explanation for a possibility of using DI not only to estimate the degree of irreversible organ damages in a specific patient, but also to choose more adequate therapy. According to the guidelines of the US Food and Drug Administration (FDA) and the European League Against Rheumatism (EULAR), DI along with activity indices (SLEDAI, BILAG) is indicated to be included in the comprehensive assessment of performed therapy in patients with SLE.